Peran Pekerja Sosial dalam Proses Adopsi Anak di Daerah Kota Medan - Dinda Pratiwi; Fajar Utama Ritonga (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2024)
Child adoption is a practice that has long been known in Indonesian culture, including in the city of Medan. This tradition is carried out for various purposes, such as providing protection for children, meeting the needs of couples who do not have children, or other social and economic reasons. Even though Indonesia has regulated adoption procedures through Law Number 23 of 2002 concerning Child Protection and other implementing regulations, many adoption practices in the field are not officially recorded. This can have a negative impact on adopted children, such as unclear status. This community service program aims to increase the role of social workers in the child adoption process in Medan City. Using a participatory and collaborative approach, this activity involves seven stages: approach, assessment, plan preparation, plan formulation, implementation, monitoring and evaluation, and termination. Assistance is provided to help prospective adoptive parents (COTA) understand and undergo legal procedures. The program results show that social worker assistance increases COTA's understanding and confidence in undergoing the adoption process according to regulations. Even though there are obstacles, such as limited access to information, this program proves the important role of social workers in supporting the success of child adoption. It is estimated that collaboration between social workers, Social Services and related parties can strengthen the implementation of legal adoption and provide optimal benefits for children who need protection.